Nucleus accumbens and caudate atrophy predicts longer action selection times in young and old adults. Issue 12 (1st September 2016) - Boisgontier, Matthieu P.; van Ruitenbeek, Peter; Leunissen, Inge; Chalavi, Sima; Sunaert, Stefan; Levin, Oron; Swinnen, Stephan P.
Abstract: There is a convergence in the literature toward a critical role for the basal ganglia in action selection. However, which substructures within the basal ganglia fulfill this role is still unclear. Here we used shape analyses of structural magnetic resonance imaging data to determine the extent to which basal ganglia structures predict performance in easy and complex multilimb reaction‐time tasks in young and old adults. Results revealed that inward deformation (i.e., local atrophy) of the nucleus accumbens and caudate were predictive of longer action selection times in complex conditions, but not in easy conditions. Additionally, when assessing the relation between behavioral performance and the shape of the left nucleus accumbens in the two age groups separately, we found a significant performance–structure association in old, but not young adults. This result suggests that the relevance of the nucleus accumbens for the process of action selection increases with age. Hum Brain Mapp 37:4629–4639, 2016 . ©2016 Wiley Periodicals, Inc.